Comparison of ELISA with virus isolation for the diagnosis of genital herpes. Issue 5 (May 1985) - Alexander, I; Ashley, C R; Smith, K J; Harbour, J; Roome, A P; Darville, J M
Abstract : An enzyme linked immunosorbent assay (ELISA) system which detects and simultaneously types herpes simplex virus antigens in clinical specimens from patients with genital herpes has been compared with standard tissue culture isolation. Although more sensitive than a similar method previously described and also more sensitive than electron microscopy and immunofluorescence, ELISA did not detect all the viruses isolated in tissue culture. Costs were comparable. The speed of obtaining the result together with knowledge of the type causing infection are useful when antiviral chemotherapy is envisaged and when considering the likelihood of recurrences.